Racism in the film The Little Mermaid: Assessing its impact on social media - Jayanti , Elvira Eka; Indriani , Nova; Febrianti, Vera; Purnama , An’nisa; Afifulloh, M (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
The controversy surrounding the casting of Halle Bailey, a black actress, as Ariel in the live-action adaptation of "The Little Mermaid" has sparked discussions about racism and representation in the media. Some people have rejected the idea of a black actress playing the role of a character who was initially depicted as white. The controversy highlights the ongoing struggle for representation and diversity in the entertainment industry. This research aims to see how people respond to the film The Little Mermaid in real life with a black main character. The Little Mermaid, a Disney classic, has been controversial due to the casting of a Black actress, Halle Bailey, as Ariel in the upcoming live-action remake. Some people have refused to accept a Black actress like Ariel, which illustrates how a white-centric perspective requires a more profound understanding. The backlash against the movie has led to abysmal box office numbers in China and South Korea, showing the global reach of anti-Blackness. However, the importance of representation in media has been highlighted, and casting a Black actress as Ariel is seen as a positive step towards diversity and acceptance. The negative attention on The Little Mermaid has fueled a groundswell of support from other fans who view such anger as founded in racism.